2020
DOI: 10.1186/s12902-020-00569-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti-Müllerian hormone and testosterone in follicular growth: a cross-sectional study

Abstract: Background: Anti-Müllerian hormone (AMH) is now considered the best serum biomarker of ovarian reserve, while basal sex hormones are classic markers used for assessing ovarian reserve. The interaction between AMH and sex hormones are complicated and not sufficiently addressed. In this study, we took diminished ovarian reserve (DOR) and polycystic ovarian syndrome (PCOS) as two extremes of ovarian reserve (deficient and excessive respectively) to investigate the role of AMH and sex hormones in follicular growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 42 publications
0
29
2
1
Order By: Relevance
“…HA had a weaker relationship in our results, which differed from some previous findings which reported a positive correlation between serum AMH and TT 20 , 21 and found that AMH levels were higher in PCOS when HA was present. 22 The AMH level in the HA+non-PCOM group (1161/1631) was higher than that in the healthy control group (7.6±4.23 vs 5.57±3.31 ng/mL) in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…HA had a weaker relationship in our results, which differed from some previous findings which reported a positive correlation between serum AMH and TT 20 , 21 and found that AMH levels were higher in PCOS when HA was present. 22 The AMH level in the HA+non-PCOM group (1161/1631) was higher than that in the healthy control group (7.6±4.23 vs 5.57±3.31 ng/mL) in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study indicated that the increase of AMH is the result of HA and PCO together, consistent with previous studies [17]. The serum AMH in PCOM + non-HA group was higher in that in HA + non-PCOM group(9.57 ± 4.3 ng/ml vs 7.6 ± 4.23 ng/ml) showed that the AMH and PCOM had the strongest relationship which was determined by the intrinsic secretion characteristics of AMH, such as increased basal follicles or delayed disappearance of AMH expression, while HA has the weaker relationship which was different from some previous nding, it was reported that the positive correlation between serum AMH and total testosterone [18][19], AMH levels was higher in PCOS when HA was present [20]. In our study, the AMH level of HA + non-PCOM group (1161/1631) was higher to HC (7.6 ± 4.23 ng/ml vs 5.57 ± 3.31 ng/ml), which can be considered as the effect of HA on AMH simply without considering the false negative of the ultrasound result.…”
Section: Discussioncontrasting
confidence: 67%
“…Excess levels of AMH lead to an impaired folliculogenesis, preventing the recruitment of primordial follicles into the pool of growing follicles and reducing the responsiveness of growing follicles to FSH [ 249 , 275 , 276 , 277 ]. The increased levels of AMH may be due to HA and hyperinsulinemia, which are characteristic features of PCOS and are closely interrelated [ 249 , 273 , 278 , 279 , 280 ], as well as to an increase in blood LH levels or the sensitivity of granulosa cells to LH, typical for PCOS patients [ 280 , 281 , 282 , 283 ]. In in vitro experiments using lutein granulosa cells obtained from oligo/anovulatory PCOS women, the LH increases the AMH production, while the expression of type II AMH receptors in these cells does not change significantly.…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%